Pengembangan Media Video Animasi Terhadap Pembelajaran Ips Materi Keberagaman Budaya Bangsa Berbantuan Quizizz - Susi Susanti; Tri Joko Raharjo; Ngabiyanto Ngabiyanto (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The pandemic is very influential in the world of education, one of which is the implementation of an online learning process that has the difficulty of transferring knowledge, so we need an interactive media that is interesting, but facilitates the transfer of knowledge. The aim is to determine the design of quizizz-assisted animated video media used for social studies learning, the feasibility of quizizz-assisted animated video media used for social studies learning, and the effectiveness of the influence of quizizz-assisted animation video media on social studies learning outcomes. The research design uses Research and Development. The population in this study were students of SDN Bojong Salaman 02, West Semarang District, Semarang City, and the samples were 20 students of class IV A as the control class and 23 students of class IV B as the experimental class. Data collection techniques with tests (multiple choice questions) and non-test (observation sheets, questionnaires, interviews, documentation). Prerequisite data analysis techniques, video feasibility test, and t-test. T-test results are 8.112 greater than t-table (2.074). In conclusion, the quizizz-assisted animation video media is effective in improving learning outcomes.